(3GdHQeLI GdJdaRjhfjI HGdbfhGJ GdeZQHjI Hjf GdJQJjH GdGhdhjGJ h JMbjb GdETHGYGJ (B:s (3OQGSI ejOGfjI (B/s - (3cRhW, gTGe Hf YdGd Hf eMeOs ((3YeGf (B:s (3OGQ GefI ddfTQ h GdJhRjY ,s, 2021)
(3jYGdL GdcJGH GdGWGQ GdeaGgjej dcd ef GdHQeLI GdJdaRjhfjI h eaghe GdEYdGe eJfGhdG GdOdGdI GdGUWdGMjI dcd ef GdHQeLI GdJdaRjhfjI h GdGYdGe Ydi MOI h GdJYQjL Ydi JMOjGJgeG GdQGgfI Ke SjJe HYOgG GdbjGe HGdOQGSI JTNjUjI dMGdI GdGYdGe GdJdaRjhfj HGdeZQH h gj OQGSI ShSjh GYdGejI JfGhdJ GGdeVehf h GdLeghQ (B. (3GdOQGSI TedJ OQGSI hUajI ddHQeLII GdJdaRjhfjI ddbfGI GdGhdi GdeZQHjIs
(3HjHd(B.:(287-302)s
Keywords: (3GdEYdGe GdJdaRjhfjs; (3GdHQeLI GdJdaRjhfjIs; (3GdJdaRjhfs